2015
DOI: 10.1590/0074-02760140351
|View full text |Cite
|
Sign up to set email alerts
|

Sandfly (Diptera: Psychodidae: Phlebotominae) species diversity in an urban area of the municipality of Tapachula, Chiapas, Mexico

Abstract: Monitoring phlebotomine sandflies in urban areas is key for epidemiological studies in susceptible populations. This paper describes sandfly fauna that were present in an urban area of the municipality of Tapachula, Chiapas, Mexico, and were captured with Shannon and CDC light traps. During February and March of 2014, 1,442 sandflies were captured, specifically Lutzomyia cruciata (Coquillet) (98.8%), Lutzomyia cayennensis cayennensis (Floch and Abonnenc) (0.8%), Lutzomyia chiapanensis (Dampf) (0.3%) and Lutzom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 10 publications
0
0
0
1
Order By: Relevance
“…We found that sand fly abundance decreases due to habitat destruction by humans and that several species are absent from degraded sites (Travi et al, 2002). However, there are some species of medical importance that are tolerant to these changes and can survive in modified environments, sometimes even with high abundances compared to sylvatic or less disturbed sites (Mikery-Pacheco et al, 2015;Sánchez-García et al, 2010).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…We found that sand fly abundance decreases due to habitat destruction by humans and that several species are absent from degraded sites (Travi et al, 2002). However, there are some species of medical importance that are tolerant to these changes and can survive in modified environments, sometimes even with high abundances compared to sylvatic or less disturbed sites (Mikery-Pacheco et al, 2015;Sánchez-García et al, 2010).…”
Section: Discussionmentioning
confidence: 84%
“…This finding represents a greater risk of contact of female L. cruciata with humans entering the crop areas. This species has been recorded in urban and peri-urban areas of Campeche, Chiapas, and Quintana Roo, with high abundances, suggesting a high capacity to adapt to these modified sites (Mikery-Pacheco et al, 2015;Pech-May et al, 2016;Sánchez-García et al, 2010). Lutzomyia cruciata has also been recorded in high abundance in coffee agroecosystems in Chiapas, suggesting that Leishmania transmission is likely to occur in these sites (Pérez et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…La trampa Shannon ha sido empleada en la península de Yucatán (74, 118-124), en Chiapas (125,126). Se ha determinado que las colectas con esta trampa en Quintana Roo tuvieron la mayor influencia en los estimadores de diversidad como son las curvas de rango-abundancia y las de acumulación de especies (124).…”
Section: Trampa Shannonunclassified